Job search via social networks: An analysis of monetary and non-monetary returns for low-skilled unemployed - Gerhard Krug; Martina Rebien (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2011)
Using a search theoretical model, we analyse the effects of the information flow via social networks (friends, relatives and other personal contacts) by comparing monetary and non-monetary outcomes in obtaining jobs via networks versus formal methods. Propensity-score matching on survey data from the low-skilled unemployed is used to identify causal effects. The analysis takes into account unobserved heterogeneity by applying Rosenbaum bounds. Because of the potential ambiguity when comparing outcomes in accepted jobs, we also examine the effectiveness of job searches using social networks as a source of information compared to not using networks. We find no evidence for causal effects on monetary outcomes and, at best, only weak evidence for effects on non-monetary job outcomes. – – Ausgehend von einem suchtheoretischen Modell analysieren wir die Effekte des Informationsflusses über soziale Netzwerke auf dem Arbeitsmarkt indem wir monetäre und nicht-monetäre Erträge aus Beschäftigung vergleichen, die über soziale Netzwerke und formale Wege gefunden wurden. Um kausale Effekte zu identifizieren wenden wir Propensity-Score-Matching auf Erhebungsdaten für geringqualifizierte Arbeitslose an. Mit Hilfe von Rosenbaum-Bounds können wir unbeobachtete Heterogenität in der Analyse berücksichtigen. Da der Vergleich nach Methode der Job-Findung irreführend sein kann, untersuchen wir auch den Effekt der reinen Jobsuche über soziale Netzwerke, unabhängig von der Methode der Job-Findung. Die Analyse zeigt keine Effekte sozialer Netzwerke für monetäre Erträge aus Beschäftigung und im besten Fall sehr schwache Hinweise auf kausale Effekte für nichtmonetäre Erträge.
Keywords: J64; J31; 330; unemployment; social networks; job search behavior; Arbeitsuche; Soziales Netzwerk; Ungelernte Arbeitskräfte; Arbeitslosigkeit; Ökonomischer Anreiz; Deutschland